Combination antiviral and anti-inflammatory therapy mitigates persistent neurological deficits in mice post SARS-CoV-2 infection - Abhishek Kumar Verma; Lu Tan; Noah Schuster; Skyler L. Moye; Li-Chun Lin; Shea Lowery; Eazhisaivallabi Duraisami; Juan E. Abrahante Lloréns; Qiang Qiu; Marco Hefti; David K. Meyerholz; Mitchell C. Coleman; et al. (Proceedings of the National Academy of Sciences, 2026)
Post-acute sequelae of COVID-19 (PASC) encompasses persistent neurological disease, including olfactory and cognitive dysfunction. The basis for this dysfunction is poorly understood. Here, we report neurological dysfunction for at least 120 d postinfection in mice infected with a virulent nonneurotropic mouse-adapted SARS-CoV-2. Long after recovery from nasal infection, we observed diminished tyrosine hydroxylase expression in olfactory bulb glomeruli and in substantia nigra. Similar changes were observed in brains of COVID-19 deceased patients. Vulnerability of dopaminergic neurons in these brain areas was accompanied by increased proinflammatory cytokines, and neurobehavioral changes. RNAseq analysis unveiled persistent microglia activation, similar to human neurodegenerative diseases. Treatment with antivirals (nirmatrelvir and molnupiravir) at the time of infection minimally prevented neurological abnormalities, consistent with patient data. In contrast, antivirals plus corticosteroids resulted in nearly complete recovery of neurological function. Remarkably, initiation of combined therapy even three days after infection improved outcomes. Together these results demonstrate that neurological dysfunction in SARS-CoV-2 infected mice resembles human neurodegenerative disease and indicate that minimizing inflammation early after SARS-CoV-2 infection may be critical for decreasing neurological PASC. The requirement for decreasing inflammation soon after infection may also explain why antiviral therapy has had inconsistent effects in patients.